Work from Home and Millennials Employee Performance: A Systematic Literature Review - Geo Farly Kalesaran; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The shift toward Work from Home (WFH) arrangements following the COVID-19 pandemic has significantly transformed workplace dynamics, especially affecting millennial employees who now make up the largest segment of the global workforce. This study aims to systematically review existing literature to understand how WFH influences the performance of millennial workers. Utilizing the PRISMA method, a total of 20 peer-reviewed journal articles published between 2020 and 2023 were selected through a rigorous screening process from major databases including Scopus, ScienceDirect, and Google Scholar. The review sample includes studies primarily using quantitative methods and focused on organizational behavior, human resources, and remote work performance. Findings reveal that WFH has both positive and negative effects on millennial performance, with key influencing factors including digital competency, organizational support, motivation, and work-life balance. The study offers practical implications for organizations seeking to optimize remote work strategies for millennials and provides a foundation for future research on generational performance in digital work environments.